Navigating the Personal Challenges and Sociopolitics of Doctoral Supervision. Issue 3 (2nd September 2019) - Richards, K. Andrew R.; Fletcher, Tim
ABSTRACT: Faculty members are important agents in the socialization of doctoral students into academia, but little training is available in preparation for the role of doctoral supervisor. In this self-study, we consider the personal and sociopolitical challenges that Kevin faced as an early career teacher education faculty member who had just begun supervising doctoral students. Data sources included Kevin's reflective journal and regular debriefing discussions between Kevin and his critical friend, Tim. Data were analyzed with a focus on identifying turning points in Kevin's understanding of his practice. This resulted in the construction of three themes related to (a) subjective theories drive doctoral education, (b) working through insecurities and the imposter syndrome, and (c) the sociopolitics of higher education. Results are discussed with reference to the self-study literature and socialization into higher education faculty roles. Recommendations are provided for the preparation of faculty member to fill roles as doctoral supervisors.